A study on epidemiological determinants and reproductive health practices among female commercial sex workers of Dharwad district - Bathija, Geeta V.; Gajula, Madhavi (International Journal Of Community Medicine And Public Health, 2017)
Background: Prostitution is linked with many socio-demographic disadvantages like minority status, low income and education level, frequent harassment by family and police and social stigma. Methods: It’s a cross-sectional study, done among female commercial sex workers. A sample of 100 women was chosen conveniently, for a study period of 2 months i.e. May and June 2015. The women were one-one interviewed in depth by a semi-structured questionnaire, finalized after Pilot testing. The data was entered into MS Excel, analysed using SPSS v 20.0 and data was presented as means and percentages. Results: 48% of the study sample belonged to the age group of 30-39. 50% of the study samples were involved in home based sex trade, 6% in brothel and 8% in public streets. All of them reported some sort of STI symptom, 39% reported burning micturition, itching and genital sores and 28% reported excessive white discharge. Regarding violence and harassment, 65% faced domestic violence at home, 37% experienced sexual violence like beatings, burning of private parts and forcible sex without payment. 31% had experienced harassment by unnatural sex. Conclusions: Poverty was cited as the most common reason for getting into this trade with half of their families being unaware of it and for a very meagre pay. Removal of social stigma can help in rehabilitating these women back into the society.